The Emancipatory Potential of Danuta Wałęsa’s Biographical Narration in the Book Dreams and Secrets. What Narrative Critical Research Unmasks? - Nowak-Dziemianowicz, Mirosława (Qualitative Research in Andragogy: Polish Research Experiences, 2026)
Interpretation of Danuta Wałęsa’s narration included in the presented study is based on specific assumptions of social ontology, epistemology and methodology. As for the nature of social existence, the vision of interpretative sociology was adopted. It consists of, among others: the belief in the processual nature of social reality; the belief that people give meaning to their actions; and also that it is possible to discover and learn about subjective aspects of social by examining respondents’ statements obtained during narrative interviews, or personal documents – like for example autobiographies. An example of such a personal document is the autobiographical book by Danuta Wałęsa entitled Dreams and Secrets. The study of Danuta Wałęsa’s biography was based on the analysis of the narrator’s life course, on searching for relationships between her own needs, decisions and social orders, norms or patterns. An attempt was also made to reconstruct this biography in orderto search for rules of selection and combining events and experiences told by the narrator.